Comparative clinical outcomes after thymectomy for myasthenia gravis: Thoracoscopic versus trans-sternal approach - Siwachat S. (2017)
© 2016. Background: Thymectomy is an effective treatment option for long-term remission of myasthenia gravis. The superiority of the trans-sternal and thoracoscopic surgical approaches is still being debated. The aims of this study are to compare postoperative outcomes and neurologic outcomes between the two approaches and to identify prognostic factors for complete stable remission (CSR). Methods: Myasthenia gravis patients who underwent thymectomy with trans-sternal or thoracoscopic approach in MahaRaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand between January1, 2006 and December 31, 2013 were retrospectively reviewed. The endpoints were postoperative outcomes and cumulative incidence function for CSR. The analysis was performed using multilevel model, Cox's proportional hazard model, and propensity score. Results: Ninety-eight patients were enrolled in this study: 53 in the thoracoscopic group and 45 in the trans-sternal group. There were no significant differences between groups in composite postoperative complications, surgical time, ventilator support days, and length of intensive care unit stay. Intraoperative blood loss and length of hospital stay were significant less in the thoracoscopic group. The CSR and median time to remission were not significantly different between the two approaches. Prognostic factors for CSR were nonthymoma (hazard ratio: 3.5, 95% confidence interval: 1.01-12.22) and presence of pharmacological remission (hazard ratio: 24.3, 95% confidence interval: 3.27-180.41). Conclusion: Thoracoscopic thymectomy is safe and provides good neurologic outcomes in comparison to the trans-sternal approach. Two predictive factors should be considered for CSR. Further prospective studies with a larger sample size and longer follow-up period are warranted to confirm these results.